Fenomena Mengemis Secara Online di Media Sosial dalam Tinjauan Hukum Islam - Fuadi Isnawan (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This study aims to examine the views of Islamic law regarding the phenomenon of online begging and the nature of work in Islam. The research method in this research is normatively that will examine these problems will be examined regarding the teachings of the Qur'an and hadith regarding this matter. The results obtained are that begging online is illegal because it is deceitful and takes advantage of certain people's circumstances in order to get as many gifts as possible. The essence of work in Islam is to worship, in addition to fulfilling one's own needs. This is done as a real form of human servitude. The conclusion of this paper is for those who are still powerful and strong, it is forbidden to beg, either online or conventionally because of Allah swt. curse them in the hereafter. Ethics in work is important, because in Islamic teachings, work must be earnest and must have a work ethic that will get the pleasure of Allah swt.